El glifosato en el Perú: entre el riesgo y la justificación del Gobierno para no prohibirlo - Llanos Puga, Cesar Manuel (2025)
Glyphosate, despite posing risks to human health and the environment, is one of the most widely used agrochemicals in Peru and globally. Motivated by this, the present research explores the reasons behind the regulatory gap in its prohibition, considering that the Peruvian legal framework assigns clear responsibilities to certain authorities in the regulation of agricultural pesticides. The study departs from a technocratic view of risk and seeks to understand how government actors justify the continued existence of the risk. Thus, the central question is: How do governmental actors responsible for regulating the use of agricultural pesticides in Peru neutralize the risk associated with glyphosate use? To answer this, interviews were conducted with government representatives, accompanied by a document review of official reports. The findings revealed how government actors legitimize the use of glyphosate through techniques such as denial of responsibility, appeal to higher loyalties, defense of necessity, affirmation of a net positive impact, justification by comparison, and promotion of a systemic perspective. These rationalizations, linked to the actors' conception of risk, revealed various arguments to justify the non-prohibition of glyphosate. Additionally, the research contributes to the theoretical evolution of the concept of risk neutralization and to the understanding of issues related to the permissiveness of using hazardous chemical products, offering perspectives on the complex dynamics of pesticide regulation and risk management in Peru.